2006
DOI: 10.1113/expphysiol.2005.032078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and osmotic pressure on Na+ transport and tissue conductance of sheep isolated rumen epithelium

Abstract: The intention of this study was to determine the effects of mucosal osmotic pressure on transport and barrier functions of the rumen epithelium of sheep, which were fed various diets: hay ad libitum, or 600, 1200 or 1800 g day -1 of a supplemented diet plus hay ad libitum. The experiments were conducted by using the conventional Ussing chamber technique. Mucosal osmolarity was adjusted to 300 (control), 375 or 450 mosmol l -1 . Feeding of a supplemented diet led to a significant increase of mucosal to serosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 67 publications
4
39
2
Order By: Relevance
“…The similar morphological changes as in our current study were presented in the acid-treated RE in vitro study, and these morphological alterations were accompanied by an increase in tissue conductance and J ms Na, which indicates passive permeability (9). Evidence also exists that the high-concentrate diet feeding (grain as in the present study) increased the ruminal epithelial passive permeability in Ussing chamber experiments (19,20). These earlier findings are in a good agreement with the assumption of increased passive permeability during HG diet feeding in the present study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The similar morphological changes as in our current study were presented in the acid-treated RE in vitro study, and these morphological alterations were accompanied by an increase in tissue conductance and J ms Na, which indicates passive permeability (9). Evidence also exists that the high-concentrate diet feeding (grain as in the present study) increased the ruminal epithelial passive permeability in Ussing chamber experiments (19,20). These earlier findings are in a good agreement with the assumption of increased passive permeability during HG diet feeding in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…Rapidly fermentable nonstructural carbohydrates increase the rate of fermentation acid production in the rumen, and the accumulation of the acids leads to a decrease in ruminal pH, hyperosmolarity, and an increase in ruminal toxin concentration (2,29). Previous studies have investigated the specific effect of low pH (9,26), hyperosmolarity (20,34), or an exposure to toxins (7) on ruminal epithelial barrier function in vitro. It should be acknowledged that any one or the combination of these factors may affect epithelial barrier function.…”
mentioning
confidence: 99%
“…Therefore, this effect may not be observed in a mild episode of SARA for a few hours or a few days (Khafipour et al, 2009b;Penner et al, 2010;Li et al, 2012b). In contrast, evidence suggests that prolonged increases in grain feeding may cause epithelia of the digestive tract of cattle to adapt, enhancing epithelial barrier function (Lodemann and Martens, 2006). Although the increase in LPS in the rumen Gozho et al, 2007) and in the hindgut (Li et al, 2012b) due to high-grain diets has been confirmed repeatedly, there is little information about such increases in other sites of the digestive tract, such as the jejunum and ileum.…”
Section: Introductionmentioning
confidence: 77%
“…Immediately after feed intake, the osmotic pressure increases from 350 to 400 mOsm and then decreases gradually over a period of 8 to 10 hours. The osmotic pressure increases with the presence of VFAs produced by fermentation processes and has a direct relationship with the pH in diets rich in carbohydrates (Lodemann and Martens 2006).…”
Section: Physicochemical Properties Of the Rumenmentioning
confidence: 99%
“…This may be due to the imbalance of intracellular hydrogen ions (Russell and Wilson 1996). The osmotic pressure in the rumen depends on the presence of ions and molecules, which generate a gas tension (Lodemann and Martens 2006). The ruminal fluid osmolality is approximately 250 mOsm/kg.…”
Section: Physicochemical Properties Of the Rumenmentioning
confidence: 99%